Cover Image. (15th December 2020) - Silva, Ana L.R.; Ribeiro da Silva, Maria D.M.C.
Abstract : The cover image is based on the Research Article Effects of the functional groups amino and nitro on the reactivity of benzoxazoles and comparison with homologous benzothiazoles by Ana L.R. Silva and Maria D.M.C. Ribeiro da Silva, https://doi.org/10.1002/poc.4118 .